Parental approaches to sexual and reproductive health information communication with adolescents in Ghana - Agyei, Frank B.; Kaura, Doreen K.; Bell, Janet D. (Frontiers in Public Health, 2025)
BackgroundParent-adolescent sexual and reproductive health (SRH) communication is recognized as an important protective factor against risky sexual behaviors and associated health problems, such as sexually transmitted infections (STIs) and unintended pregnancies. This study explored the specific approaches Ghanaian parents use to communicate SRH information to their adolescents.MethodsThis study employed a qualitative descriptive design to conduct interviews with 10 parents, with the sample size determined by data saturation. Participants were selected through purposive sampling from Asante Akyem North Municipality in Ghana. Thematic analysis was conducted inductively, following Braun and Clarke's approach.FindingsTwo broad themes emerged: timing of sexual and reproductive health information communication and sexual and reproductive health information communication style. This study highlights varying parental approaches to sexual and reproductive health communication, ranging from proactive and open to authoritative communication.ConclusionThe findings underscore the complexity of parent-adolescent SRH communication, shaped by cultural norms, parental comfort levels, and perceived adolescent maturity. This highlights the need for interventions that enhance parent-adolescent communication skills.